2016
DOI: 10.1021/acs.jpcc.5b11844
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CO2 and CH4 with Functionalized Periodic Mesoporous Phenylene–Silica: Periodic DFT Calculations and Gas Adsorption Measurements

Abstract: Non-functionalized and functionalized periodic mesoporous phenylene-silicas (Ph-PMOs) with different kinds of amine groups were prepared and their capacity to uptake CO2 and CH4 molecules were experimentally evaluated considering biogas upgrading. It was found that aminopropyl groups grafted to the free silanols of the Ph-PMO displayed the highest selectivity for CO2 gas, adsorbing 26.1 times more CO2 than CH4 at 25 C. The interaction effect of the surface of these materials with the CO2 or CH4 molecules was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 46 publications
8
58
1
Order By: Relevance
“…Thus, the CO 2 -CH 4 selectivities calculated for BCNO MBG1 and BCNO MBG2 from their respective k H values were again remarkable, in the upper range of figures found for some of the most efficient adsorbents reported to date -e.g. see data inTable 2for porous carbons, POFs, zeolites and MOFs 55,60,61,64,68,72,73,74,75,76,77. 4.…”
mentioning
confidence: 99%
“…Thus, the CO 2 -CH 4 selectivities calculated for BCNO MBG1 and BCNO MBG2 from their respective k H values were again remarkable, in the upper range of figures found for some of the most efficient adsorbents reported to date -e.g. see data inTable 2for porous carbons, POFs, zeolites and MOFs 55,60,61,64,68,72,73,74,75,76,77. 4.…”
mentioning
confidence: 99%
“…Thus far, selectivity for CO 2 /CH 4 separation for different functionalized PMOs has been evaluated by using experiments [30,31], while the CO 2 and CH 4 adsorption mechanisms involved in this materials were clarified using periodic density functional theory (DFT) calculations [30]. In fact, as we have observed, experimental gas adsorption data and computational studies are in good agreement and such DFT results proved also useful to guide the preparation of more efficient PMO materials.…”
mentioning
confidence: 79%
“…Additionally, Ph-PMOs display a narrow distribution of both meso-and molecular-scale periodicities; a clear advantage for adsorbate diffusion within the pore channels. Moreover, we have seen [30,31] that the modification of the Ph-PMO with amine groups allows the optimization of their properties for the separation of CO 2 /CH 4 , by improving the interaction with the CO 2 molecule. Recently, we demonstrated that aminopropyl groups grafted to the free silanols of Ph-PMO promote selectivity for CO 2 /CH 4 separation making the resulting APTMS@Ph-PMO so far the most selective of all PMOs applied in this field, at 25 °C adsorbing 26.1 times more CO 2 than CH 4 , as determined by the ratio of Henry constants [30].…”
mentioning
confidence: 99%
“…demonstrated that amine groups could be functionalized in the PMOs through mononitration with nitric acid in the presence of sulphuric acid, followed by the reduction with tin chloride and HCl. The amine‐functionalized samples showed higher selectivity for the adsorption of CO 2 molecules in comparison with the CH 4 molecules . The same group also manipulated the amine‐functionalized PMOs for the formation of dialkylated amine through the microwave‐assisted approach.…”
Section: Synthesis Of Organo‐functionalized Molecular Sievesmentioning
confidence: 99%